Juan García del Río: The first chancellor of Peru - Chanamé Orbe, Raúl (2021)
Peru was born as a reference in Public International Law as the Southern Liberation Expedition, with the Treaty signed by the State of Chile and the United Provinces of Río de la Plata (1819). In all these legal acts preparatory to independence, Juan García del Rio, friend and Secretary of Government of José de San Martín, participated prominently. García was the protagonist of the Peace Conference with the delegates of Virrey Pezuela, Commissioner Regio Abreu and Viceroy La Serna. When the Protectorate was established (1821), he was part of the first cabinet, as Secretary of Government and Foreign Relations of the new Peruvian government, being considered for this reason as the first Chancellor of the Peruvian State.